African religion and politics: redefinition of the past - Matiza, Vimbai M. (Open Science, 2016)
The paper is addressing the concept of African religion and politics thus redefining the traditional past of the African people. The argument of the article is taken from Ngugi's assertion that the African novelist has attempted to restore the African people through characterization in different works of art to his history. It is from this angle that the article has selected three works of art to demonstrate and illustrate the point. The ideas are also backed up by two theories, the Afro centric view and Negritudism. These theories found their way into the paper because of their strong bearing on the indigenous people. In light of this view the paper therefore will address the religion of the African people, how they conducted their politics, the position of women in politics, their belief systems and way of life hence repositioning them to their past experiences. It is against this condition that the article selected Mutasa's Nhume yaMambo (1990), Achebe's Arrow of God (1964) and Cesaire's A Notebook of a Return to my Native Land (1995) lay bare that Africans had a way of conducting their life prior to colonialism.